Preparation, structural characteristics and immune regulatory effects of Codonopsis pilosula polysaccharides: a review - Pan, Meitong; Zhang, Xiaozhuang; Huang, Shumin; Liu, Meiqi; Song, Shiyi; Ma, Junbai; Li, Chenliang; Ma, Wei; Liu, Xiubo (Frontiers in Immunology, 2025)
Codonopsis pilosula polysaccharides (CPPs), a class of representative bioactive compounds derived from Codonopsis pilosula, have attracted considerable attention recently as natural immunomodulators due to their wide range of biological activities and favorable safety profile. This review provides a comprehensive overview of recent advances in the extraction and purification methods, chemical structural features, immunomodulatory mechanisms, and the impact of structural modifications on the immunological functions of CPPs. Notably, this work emphasizes the integration of structural modification strategies with immunomodulatory mechanisms, a perspective rarely highlighted in previous reviews. Special attention is given to the macrophage-centered TLR4/MyD88/NF-κB signaling pathway, which plays a pivotal role in coordinating adaptive immune responses through cytokine-mediated interactions with T and B lymphocytes. Structural modification strategies, such as sulfation, phosphorylation, selenization, and nano-carrier incorporation, have significantly enhanced the stability, bioavailability, and immunoregulatory effectiveness of CPPs. Furthermore, this review addresses current challenges, including structural heterogeneity, lack of standardization, and limited clinical evidence. This work aims to provide a valuable reference for future research and applications of CPPs as immunotherapeutic agents and functional food ingredients.